Students' Perceptions of Parental Social Support and School Climate in Fostering Students' Learning Motivation in Islamic Religious Education (PAI) Subjects at SMA 1 Sewon Bantul Yogyakarta - Rahmawati, Arlina; Makrufi, Anisa Dwi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
The low learning motivation of students in Islamic Religious Education (PAI) subjects has become an important concern because it directly impacts learning achievement and student engagement in the classroom. This research aims to reveal students' perceptions of parental social support and school climate in shaping their learning motivation in PAI subjects. The approach used is qualitative descriptive with data collection techniques through interviews and questionnaires. Participants consisted of students, parents, and PAI teachers at SMA Negeri 1 Sewon Bantul. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The research results indicate that parental support is primarily in the form of emotional and spiritual support, such as providing encouragement, offering prayers, and providing learning facilities at home, rather than direct academic assistance. The religious, conducive school climate, supported by teachers' enjoyable approaches, also strengthens students' learning motivation. In conclusion, students' learning motivation is formed through collaboration between internal drive and external environment, particularly from family and school. This research highlights the importance of continuous collaboration between parents and schools in creating a supportive learning environment that motivates students in PAI learning